Пока гром не грянет...: [повести] / Марина Серова - Серова Марина Сергеевна (Русский бестселлер, 2000)
Экземпляры: ф.18 (2001) / Инвентарный номер: 43161 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44